„W stronę biografii totalnej?” Buty Ikara Mariana Buchowskiego wobec projektu pisarskiego Edwarda Stachury – szkic krytyczny - Szumański, Borys (Poznańskie Studia Polonistyczne. Seria Literacka, 2016)
This critical sketch is dedicated to a new biography of Edward Stachura by Marian Buchowski. A writer like Stachura, whose work is very closely intertwined with his life (at least in his declarations) is a challenging protagonist for a biography. In this article, attempts are made at following the way in which Buchowski tries to bring out another human being in the text. His ideas are juxtaposed and confronted with Stachura’s own life-and-art ideas, as to him looking for various methods of recording existence was among the crucial goals of writing. As a result, the thesis is put forward that some sort of a writer’s “totality” is a feature linking Stachura and Buchowski. In this context, the biography written by Buchowski is not only of importance to research into Stachura’s writing but also a significant countersignature of his work.